Significance of the Influence of Leadership Model, Morale, and Satisfaction on Performance Consistency - Nurbaeti, Siti (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2022)
Maintaining performance while carrying out tasks is not easy, many things make emotions and work behavior inconsistent. Therefore, external factors are needed as a reminder, for example the role of leadership. The presence of the leader is one of the factors of self-control in carrying out tasks, because its presence is considered to be a supervisor for the implementation of tasks. In addition, self-factors such as a sense of morale and job satisfaction are internal factors that affect performance consistency. This research was conducted, to be able to see the role of internal and external factors of employees on the consistency of performance in carrying out their duties. The method used is quantitative with statistical regression. The research subjects were teachers at a boarding-based Islamic school in the city of Bogor. A total of 41 respondents were used for questioning through the census technique. The results of the study explain that a good leader can be a motivation for employees in carrying out their duties. Because employees feel, cared for and recognized their existence. In addition, the factors of enthusiasm and job satisfaction are factors that are thought to be able to increase self-enthusiasm in carrying out tasks.